Production of platelet-rich plasma gel from elderly patients under antithrombotic drugs: Perspectives in chronic wounds care. (4th July 2018) - Velier, M.; Magalon, J.; Daumas, A.; Cassar, M.; Francois, P.; Ghazouane, A.; Philandrianos, C.; Bertrand, B.; Frere, C.; Bernot, D.; Villani, P.; George, F. Dignat; et al.
Abstract: Platelet-Rich Plasma (PRP) is an autologous biological therapy obtained by centrifuging the patient's own blood to concentrate platelets. The addition of autologous thrombin and calcium chloride to PRP allows the production of a semi-solid form called PRP gel. PRP gel is increasingly used in a variety of tissue defects and predominantly in the management of non-healing chronic wounds. The topical application of PRP gel seems promising due to the capability of platelets to store and secrete growth factors (GF), fibrin and cytokines, which are essentials for wound healing. Most patients who suffered from chronic wounds are elderly patients with co-morbidities and polypharmacy including antithrombotic drugs such as antiplatelet agents (AP) or anticoagulants (AC), which could hamper the feasibility of this autologous platelet-derived therapy. To date, no study has investigated PRP gel formation in patients with AP or AC. The aim of this study was to evaluate the influence of AP or AC drugs on the production of PRP gel formation from elderly patients. Different biological characteristics were determined to qualify the production of PRP gel from such patients (Interquartile range (IQR) = 75–92 years) compared to healthy volunteers (IQR = 23–37 years). No significant difference was observed in the volume, composition (quantity of platelets, leukocytes and red blood cells) and functionality of platelets from PRP except a higher ADP-induced P-selectin expression in healthy donors compared with elderly patients. Autologous thrombin characteristics were similar in the two groups. Gel time formation (IQR: 120–195 seconds for controls and 135–210 seconds for elderly patients) and final composition of PRP gel were not significantly modified. Concentrations of theoretical thrombin generated in the serum and in the gel were inversely correlated with the time of formation of PRP gel (r 2  = 0.57, p = 0.012). Altogether these data indicate that PRP gel preparation is not impacted by the use of antithrombotic drugs. Such results support the feasibility of using this innovative autologous biotherapy in the management of elderly patients with non-healing chronic wounds.